MINAT BERWIRAUSAHA DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Widhiastuti, Ni Luh Putu; Dewi, Ni Luh Putu Sandrya (Jurnal Riset Akuntansi (JUARA), 2020)
Entrepreneurial interest is the desire, self-confidence and stability of an individual in facing all the possibilities that occur with full confidence to create jobs for him self and others. Entrepreneurial interest needs to be increased considering unemployment is an old problem that must be built. The research objective was to determine the effect of entrepreneurial learning, entrepreneurial motivation, personality, family and social environment on interest in entrepreneurship. The method of determining the sample used is the Slovin method. Sample of students of the Accounting Study Program, Faculty of Economics and Business, Mahasaraswati Denpasar University class of 2017 and 2018 with the data analysis technique used in this study is multiple linear regression analysis. The results showed that entrepreneurial learning, motivation, family environment and social environment had a positive effect on interest in entrepreneurship, while the influence had a negative effect on interest in entrepreneurship.